Pemberdayaan Masyarakat Revolusi Mental Melalui Gerakan Literasi Sekolah - Amaliati, Siti; Maani, Arifatul; Anggraeni, Desi; Fajriani, Adinda Nurul; Widadi, Nurul; Farthonia, Romy Thoriq; Zainullah, Muhammad Haris; Masitho, Dewi (EL-EMIR INSTITUTE, 2024)
The community service activity titled